KEWENANGAN PEMERINTAH DAERAH DALAM PENGELOLAAN PERTAMBANGAN MINERAL DAN BATUBARA - Hartati Hartati (Masalah-Masalah Hukum, 2012)
Abstract The research have aimed to  study about trend of damage on the environment function of the mining activities on local governance of  autonomy era. In this research, the subject  matter will be analyzed  by the authorized of management on  mineral and coal that inherent on  the local government than the regulation perspective. The research showed that, rather than a regulatory issue or arrangement, perspective and orientation in the understanding of decentralization and regional autonomy were subsequently embodied in the decisions and public policies are considered more to be related to the above issues. In this case, decentralization and local autonomy understood merely as a matter of institutional, while the capacity issues with regard to the involvement of community participation, public oversight and public accountability at the local level, not too overlooked. There are Implication, reforming decentralization and regional autonomy in the management of mineral mines and coal only produces the birth of management authority  for  the local government, wealth, and distribution revenue to the area, while the matter involving public participation and oversight and public accountability over management is being neglected. Keyword: Management of mineral mines and coal, decentralization, local authorities. Abstrak Penelitian ini bertujuan mengkaji kecenderungan terjadinya kerusakan fungsi lingkungan akibat kegiatan pertambangan pada pemerintahan otonomi daerah sekarang ini. Di dalam penelitian ini, persoalan tersebut akan dikaji melalui kewenangan pengelolaan pertambangan mineral dan batubara yang ada pada pemerintah daerah. Hasil penelitian menyimpulkan bahwa, daripada persoalan regulasi atau pengaturannya, cara pandang dan orientasi dalam memahami desentralisasi dan otonomi daerah yang kemudian diwujudkan dalam keputusan dan kebijakan publik dinilai lebih memiliki keterkaitan dengan persoalan di atas. Dalam hal ini desentralisasi dan otonomi daerah dipahami sebatas sebagai persoalan kelembagaan, sementara masalah peningkatan kapasitas negara yang berkenaan dengan pelibatan partisipasi masyarakat, pengawasan masyarakat, dan pertanggungjawaban publik di tingkat lokal, tidak terlalu dipentingkan. Implikasi-nya, reformasi desentralisasi dan otonomi daerah di bidang pengelolaan pertam-bangan mineral dan batubara hanya menghasilkan lahirnya kewenangan pengelolaan pada pemerintah daerah, adanya pembagiaan kekayaan, dan pendis-tribusian pendapatan ke daerah; sedangkan soal pelibatan partisipasi dan pengawasan masyarakat serta pertanggungjawaban publik atas pengelolaan tersebut menjadi terabaikan. Kata Kunci: Pengelolaan Mineral & Batu Bara, Desentralisasi, Kewenangan Pemerintah Daerah.